Ambiente de desenvolvimento de drones com ROS2, Linux embarcado e Matlab - Francisco, Mateus Gava (Universidade Federal de São Carlos, 2026)
Humanity has long dreamed of robots performing a wide variety of functions; nowadays, this is closer to reality than one might imagine. Given the explosion and spread of robot use, and the advent of drones, building and designing these machines has become increasingly challenging. To remedy this situation, various technologies have emerged, such as powerful and compact middleware and hardware, as well as development and testing techniques that have accelerated and reduced the cost of drone design. However, testing these aircraft quickly and safely during their development has become a challenge. To mitigate this problem, this work seeks to conceptualize an environment capable of assisting drone development, using software and hardware-in-the-loop techniques, aligned with the use of embedded systems, simulations, and a physical model of one of the drone’s axes. Preliminary results show that embedded Linux is capable of controlling the simulation stably and with tolerable latency values.
Drone development environment with ROS2, embedded Linux, and Matlab
Keywords: Middleware; Hardware; Testes; Drone; ENGENHARIAS::ENGENHARIA ELETRICA; 9. Indústria, Inovação e Infraestrutura